Pengembangan Bahan Ajar IPS Terpadu Kelas VIII untuk Tema Keunggulan Iklim Indonesia di SMP 2 Talun Kabupaten Pekalongan - KURNIA, ANIS (2016)
Anis Kurnia. A610110030. THE DEVELOPMENT OF TEACHING MATERIAL OF INTEGRATED SOCIAL SCIENCE OF THE 8TH GRADE FOR THE THEME OF INDONESIAN CLIMATE EXCELLENCE AT SMP 2 TALUN OF PEKALONGAN REGENCY. Thesis. Teacher Training and Education Faculty, Muhammadiyah University of Surakarta, 2015. This research was based on the background that the insight of disaster in school is low because the lack of teaching material which is able to motivate students in learning the disaster. The development of teaching material of disasteris needed to be conducted, therefore, it can help the students in learning disaster. The objectives of this research were: (1) to make criteria of teaching material of Integrated Social Science needed by the students, (2) to make a model and teaching material of Integrated Social Science for the 8th students, (3) to know the effectiveness of teaching material which had been developed with a sub theme "The Indonesian Climate Excellence". Type of this research used the procedures of Research and Development (R & D). R &D is a process or steps to develop a new product. Based on the needs analysisof teaching material, the students and the teacher needed material containing the nature of disaster and problem exercises which is displayed in short and concise and conveying the learning objectives implicitly. The teaching material was packaged using a size of B5 using fontof timesnew roman 11 and colorful cover. It was conveyed using good, correct, and communicative language and appropriate toThe Perfect Spelling System (EYD). Then, the learning material was assessed by the expert lectures, teachers, and students based on per aspect (contect/ material, presentation, graphic, and language). Obtaining an average score of 81.8 was included as a very good category. To know the effectiveness of learning material, it could be seen through the learning processes in the forms of pretest and posttestin the experimental class and controlclass. In the controlclass which had no treatment, it obtained an average score of 64.13 in the pretest and 64.13 in the posttest, meanwhile, in the experimental class, it obtained an average score of 64.63 in thepretest and then the average score increased into 98.38 in the posttest (after obtaining treatment using the teaching material developed by the researcher). Therefore, it can be concluded that the book "The Excellence of Indonesian Climate and The Weakness of Indonesian Climate" was successful in planting the insight of disaster, or in other words, the book was effective.